230k views
3 votes
Solve −2x2 +3x − 9 = 0. (2 points)

User Daren
by
5.2k points

1 Answer

2 votes

Answer:

3

Explanation:

2x^2 + 3x - 9 = 0

The quadratic is not factorable so quadratic formula must be used.

x = (-b + - √(b^2 - 4ac))/2a

a = -2, b = 3, c = -9

x = (-3 + - √(9 - 4*-2*-9))/-4

x = (-3 + - √(-63))/-4

x = -3 + - 3i√7

--------------

-4

x = 3 + 3i√7 x = 3 - 3i√7

------------ ------------

4 4

User Philo
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.